Phthalates and thyroid function in preschool age children: Sex specific associations. (September 2017) - Morgenstern, Rachelle; Whyatt, Robin M.; Insel, Beverly J.; Calafat, Antonia M.; Liu, Xinhua; Rauh, Virginia A.; Herbstman, Julie; Bradwin, Gary; Factor-Litvak, Pam
Abstract: Background: Research relating either prenatal or concurrent measures of phthalate exposure to thyroid function in preschool children is inconclusive. Methods: In a study of inner-city mothers and their children, metabolites of di-n-butyl phthalate, butylbenzyl phthalate, di-isobutyl phthalate, di(2-ethylhexyl) phthalate, and diethyl phthalate were measured in a spot urine sample collected from women in late pregnancy and from their children at age 3 years. We measured children's serum free thyroxine (FT4) and thyroid stimulating hormone (TSH) at age 3. Linear regression models were used to investigate the associations between phthalate metabolites, measured in maternal urine during late pregnancy and measured in child urine at age 3 and thyroid function measured at age 3. Results: Mean concentrations (ranges) were 1.42 ng/dL (1.02–2.24) for FT4, and 2.62 uIU/mL (0.61–11.67) for TSH. In the children at age 3, among girls, FT4 decreased with increasing log e mono-n-butyl phthalate [estimated b = − 0.06; 95% CI: (− 0.09, − 0.02)], log e mono-isobutyl phthalate [b = − 0.05; 95% CI: (− 0.09, − 0.01)], log e monoethyl phthalate [b = − 0.04; 95% CI: (− 0.07, − 0.01)], and log e mono(2-ethyl-5-hydroxyhexyl) phthalate [b = − 0.04; 95% CI: (− 0.07, − 0.003)] and log e mono(2-ethyl-5-oxy-hexyl) phthalate [b = − 0.04; 95% CI: (− 0.07, − 0.004)]. In contrast, among boys, we observed no associations between FT4 and child phthalate metabolites at age 3. On the other hand, in late gestation, FT4 increased with increasing log e mono-(2-ethylhexyl) phthalate [estimated b = 0.04; 95% CI: (0.02, 0.06)] and no sex difference was observed. We found no associations between phthalate biomarkers measured in either the child or prenatal samples and TSH at age 3. Conclusions: The data show inverse and sex specific associations between specific phthalate metabolites measured in children at age 3 and thyroid function in preschool children. These results may provide evidence for the hypothesis that reductions in thyroid hormones mediate associations between early life phthalate exposure and child cognitive outcomes. Highlights: In a study of inner-city mothers and their children, we measured metabolites of several phthalates in maternal prenatal urine and child urine collected at age 3. We also measured serum free thyroxine and thyroid stimulating hormone in the children at age 3. We found inverse and sex specific associations between specific phthalate metabolites measured in children at age 3 and free thyroxine. The associations were limited to girls. Maternal prenatal urine concentrations of MEHP, a metabolite of DEHP, were associated with increases in free thyroxine in children at age 3. No associations were found between phthalate metabolites and thyroid stimulating hormone.